THE EFFECT OF HERRINGBONE TECHNIQUE ON STUDENTS’ READING COMPREHENSION OF THE FIRST YEAR STUDENTS AT SMP NEGERI 23 MAKASSAR - Bustang Bustang (Universitas Muhammadiyah Makassar, 2017)
The aim of his research is that want to know the herringbone technique application is effective to improve student skill in reading, predict, make the conclusion in every paragraph and able to solve the problem of students in understand reading text or discourse. This research is experimental research and conducted at SMP Negeri 23 Makassar. The total of population in Grade VII students are 480 students that shared in 12 classes. The researcher choose sample in class VII-12 are 32 students. The aim of the researcher to choose class VII12 as a subject of the research because the average of the student in this class is stillless to understand the reading text. The result of data analysis in pre-test and post-test showed that t-test score is 36.25 and t-table score is 2.036. The t-test score is better than t-table or (tt36.25 2.036). It showed that the students’ skill to understand reading text at the end of the research is improved. It can be identified with the significant different between average score in pre-test (3) and post-test 5.8). This research showed that the herringbone technique had tried at the SMP Negeri 23 Makassar and it worked. It appeared that student’s English skill in understanding reading text from bad to be better.